Human Immune System Increases Breast Cancer-Induced Osteoblastic Bone Growth in a Humanized Mouse Model without Affecting Normal Bone - Tiina E. Kähkönen; Mari I. Suominen; Jenni H. E. Mäki-Jouppila; Jussi M. Halleen; Azusa Tanaka; Michael Seiler; Jenni Bernoulli (Journal of Immunology Research)
Bone metastases are prevalent in many common cancers such as breast, prostate, and lung cancers, and novel therapies for treating bone metastases are needed. Human immune system-engrafted models are used in immuno-oncology (IO) studies for subcutaneous cancer cell or patient-derived xenograft implantations that mimic primary tumor growth. Novel efficacy models for IO compounds on bone metastases need to be established. The study was performed using CIEA NOG (NOG) mice engrafted with human CD34+ hematopoietic stem cells (huNOG) and age-matched immunodeficient NOG mice. Bone phenotyping was performed to evaluate baseline differences. BT-474 human breast cancer cells were inoculated into the tibia bone marrow, and cancer-induced bone changes were monitored by X-ray imaging. Bone content and volume were analyzed by dual X-ray absorptiometry and microcomputed tomography. Tumor-infiltrating lymphocytes (TILs) and the expression of immune checkpoint markers were analyzed by immunohistochemistry. Bone phenotyping showed no differences in bone architecture or volume of the healthy bones in huNOG and NOG mice, but the bone marrow fat was absent in huNOG mice. Fibrotic areas were observed in the bone marrow of some huNOG mice. BT-474 tumors induced osteoblastic bone growth. Bone lesions appeared earlier and were larger, and bone mineral density was higher in huNOG mice. huNOG mice had a high number of human CD3-, CD4-, and CD8-positive T cells and CD20-positive B cells in immune-related organs. A low number of TILs and PD-1-positive cells and low PD-L1 expression were observed in the BT-474 tumors at the endpoint. This study reports characterization of the first breast cancer bone growth model in huNOG mice. BT-474 tumors represent a “cold” tumor with a low number of TILs. This model can be used for evaluating the efficacy of combination treatments of IO therapies with immune-stimulatory compounds or therapeutic approaches on bone metastatic breast cancer.